An Examination of Teachers’ Perspectives on Gender Representation in a Digital Cultural Commodity –Achieve 3000- and Its Impact on English Preparatory School Students at Haliç University of Turkey - Ziba Salarvand (Asparkía)
This study investigates the effect of digital cultural commodities on English language learners in the preparatory program of Haliç University from a gender perspective. The point of view of English language teachers of preparatory program on the function of gender in digital English learning commodity, Achieve3000, is examined in this paper. The usage of digital commodities in the classroom is a way to improve student engagement and language learning. The study investigates how digital learning resources are effective for language learning and how they represent gender norms and stereotypes. English teachers perceive Achieve3000 positively for language learning, though reservations exist about its effectiveness in reading skill development and identifying student needs.